1990
DOI: 10.1042/bj2720369
|View full text |Cite
|
Sign up to set email alerts
|

Xylanase B and an arabinofuranosidase from Pseudomonas fluorescens subsp. cellulosa contain identical cellulose-binding domains and are encoded by adjacent genes

Abstract: The complete nucleotide sequence of the Pseudomonas fluorescens subsp. cellulosa xynB gene, encoding an endo-beta-1,4-xylanase (xylanase B; XYLB) has been determined. The structural gene consists of an open reading frame (ORF) of 1775 bp coding for a protein of Mr 61,000. A second ORF (xynC) of 1712 bp, which starts 148 bp downstream of xynB, encodes a protein, designated xylanase C (XYLC), of Mr 59,000. XYLB hydrolyses oat spelt xylan to xylobiose and xylose, whereas XYLC releases only arabinose from the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
1
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(139 citation statements)
references
References 31 publications
(36 reference statements)
4
132
1
1
Order By: Relevance
“…Incubations for both spectrophotometer and HPLC assays were carried out at 37 "C. Activity on de-starched wheat bran was measured both in the absence and in the presence of 2 U Tricboderma viride xylanase [Megazyme (Aust) Pty Ltd] as described previously (Faulds & Williamson, 1991). Xylanase activity was detected using standard methodology by determining the release of reducing sugar (Miller, 1959) from 1 % (w/v) soluble oat spelt xylan (Kellet et a/., 1990), and was expressed as xylose equivalents: one unit of enzyme activity released 1 pmol sugar min-' at 37 "C, pH 6.5. Acetylesterase and acetylxylan esterase activity were determined as described previously (Faulds & Williamson, 1993b).…”
Section: Methodsmentioning
confidence: 99%
“…Incubations for both spectrophotometer and HPLC assays were carried out at 37 "C. Activity on de-starched wheat bran was measured both in the absence and in the presence of 2 U Tricboderma viride xylanase [Megazyme (Aust) Pty Ltd] as described previously (Faulds & Williamson, 1991). Xylanase activity was detected using standard methodology by determining the release of reducing sugar (Miller, 1959) from 1 % (w/v) soluble oat spelt xylan (Kellet et a/., 1990), and was expressed as xylose equivalents: one unit of enzyme activity released 1 pmol sugar min-' at 37 "C, pH 6.5. Acetylesterase and acetylxylan esterase activity were determined as described previously (Faulds & Williamson, 1993b).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, CBMs acting in trans have only a minor influence on the access problem, although this might reflect the dissociation of the targeting and (possible) disrupting function of these modules. Of potential significance is the location of crystalline cellulose-specific CBMs in many enzymes that display no cellulase activity (Kellett et al, 1990;McKie et al, 2001;Hogg et al, 2003;Vincent et al, 2010), which argues against these modules having a specialized function in cellulose degradation. A more likely explanation for the capacity of CBMs to increase the activity of glycoside hydrolases against insoluble substrates is that they reduce the "accessibility problem" by bringing the appended catalytic modules into intimate and prolonged association with their target substrate, thereby enhancing catalytic efficiency.…”
Section: How Do Cbms Potentiate Catalysis?mentioning
confidence: 99%
“…Many of these enzymes, however, also contain a CBM that binds to crystalline cellulose (Kellett et al, 1990;McKie et al, 2001;Hogg et al, 2003). It has been suggested that once bound, these type A modules are able to slide across the surface of cellulose (Jervis et al, 1997), enabling the substrate-specific type B and type C CBMs to lock onto its ligand and thus direct the enzyme to its target glycosidic bonds (Kellett et al, 1990). In general, the affinity of CBMs for their target plantderived ligands is low (K d of approximately 100 mM; Boraston et al, 2004).…”
Section: Cbmsmentioning
confidence: 99%
“…All three enzymes contain an identical N-terminal region that comprises a typical family 2a CBM joined via a serine-rich linker to the X4 module (19,20). As the X4 modules in these Cellvibrio enzymes are shown to bind polysaccharides (see below), henceforth these sequences will be designated as a new family of CBMs (family 35, CBM35).…”
Section: Identification Of the Cbm35 Family Of Protein Modules-mentioning
confidence: 99%
“…This is exemplified by three plant cell wall-degrading enzymes from Cellvibrio japonicus, Xyn10B (xylanase), Abf62A (arabinofuranosidase), and Est1A (acetyl xylan esterase) that contain an identical ϳ150-amino acid module, termed X4, whose role in enzyme function is unclear (19,20). This X4 module is also present in a mannanase (Man5C) from the same organism (21).…”
mentioning
confidence: 99%